Effect Of Customer Satisfaction, Marketing Mix, And Price In Astana Anyar Market Bandung - Akhmad Baidun; Rebecha Prananta; Muhammad Ade Kurnia Harahap; Muhammad Yusuf (IAIN Palopo, 2022)
The purpose of this study was to determine the impact of marketing mix, price and customer experience on customer satisfaction at Pasar Astana Anyar Bandung. The examination procedures used in this study are validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test, determination analysis and f-test. The results of the review show that the promotion mix affects customer satisfaction at Pasar Astana Anyar Bandung. From the test results with the T test shows that the marketing mix has a significant effect on customer satisfaction. Prices affect customer satisfaction at Astana Anyar Market Bandung. From the test results with the T test shows that the price affects customer satisfaction. Customer experience influences customer satisfaction at Astana Anyar Market Bandung. From the test results with the T test shows that customer experience affects customer satisfaction. Judging from the f-test, it is found that F-count > F-table is 212,297 > 3.12, this shows that the marketing mix, price and customer experience basically affect customer satisfaction with a sig level. big. 0.000 < 0.050. is significant of costumer satisfaction